PENGARUH PERENDAMAN AIR KAPUR TERHADAP KADAR SULFAT DAN KEKUATAN GEL KARAGINAN RUMPUT LAUT Kappaphycus alvarezii - Haris, Radityo; Santosa, Gunawan Widi; Ridlo, Ali (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Gel formation is the result of crosslinking between adjacent helical chains, with sulphate groups facing to the outside. The theoretical basic is using alkaline compounds are cheap and easily available to eliminate the sulfate groups on the K-carrageenan, with the water immersion method of Ca(OH)2 to increase the degree of molecular uniformity and gel strength. This study is to determine the effect of Ca(OH)2 water immersion of sulphate content and gel strength. This study its experimental research laboratory with a completely randomized design and variations in treatment where seaweed samples were treated with submersion of Ca(OH)2 at different concentration (1.2 g/L, 0.6 g/L, and 0.3 g/L). The experiments were performed with 3 replications. The first extraction process used 5% KOH, being the second extraction used 1% KCl. Determination was carried out toward powder of carrageenan, its chemical characters (moisture content, ash, and sulphate), physical characters (viscosity, gel strength, and color of thalus) carrageenan had produced. The results showed that seaweed treated with 0.3 g/L Ca(OH)2 very significantly influent (p <0.01), produced the highest gel strength at 516.23 dyne/cm with the lowest sulfate levels at 20.84 %.